Prestige in Philanthropy : How Elite Donors and Cultural Organizations Co-Create Symbolic Capital - Kortelainen, Kaisa (My University, 2026)
The economic elite and the field of arts and culture have historically been connected by patronage and philanthropy. Elite philanthropists are often motivated by personal gain and social status, which can be achieved by acquiring favourable intangible assets, such as prestige. On the other hand, cultural organizations often rely on donations as an important source of funding, while also trying to strengthen their position within the field by enhancing their influence and legitimacy. Donors and beneficiaries thus share a mutual interest for intangible value that can be realised through a philanthropic relationship. This thesis examines the phenomenon of intangible benefits generated by donations through the lenses of symbolic capital and value co-creation theories. Conducted as a literature review, this study answers the research question: How does philanthropy co-create symbolic capital between elite donors and cultural beneficiaries? As marketing research has not previously focused on the connection between symbolic capital and value co-creation theories, nor examined these theories respectively in the context of elite donors and cultural beneficiaries, this thesis addresses this research gap and aims to provide insights into how elites and the field of arts and culture could mutually benefit from philanthropic relationships. The findings reveal that for co-creation of symbolic capital to occur, elite donors and cultural beneficiaries must engage in exchange relationships that aim to address mutually relevant matters. Beyond the money donated, the actors must also possess other types of capital, which should be readily transformable to symbolic capital. The donation must be made visible to desired social circles, as context is vital in symbolic capital co- creation. These findings suggest that the donation cannot be anonymous, highlighting the strategic importance of determining a communication strategy for the exchange. This thesis contributes to the academic discussion on symbolic capital and value co-creation theories and establishes that further studies on the relation of these theories should be conducted. The limitations of this study include its reliance on previous literature that lacks a holistic definition of elite donors. This thesis also focuses on positive symbolic capital creation and does not extensively examine the risks and negative intangible effects a donor-beneficiary relationship could produce.
Keywords: Symbolic capital; Value co-creation; Service-dominant logic; Elite philanthropy; Arts and culture